2004
DOI: 10.1128/jcm.42.9.4297-4299.2004
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance Study (2000 to 2001) of G- and P-Type Human Rotaviruses Circulating in South Korea

Abstract: Human rotavirus VP4 and VP7 gene sequences were amplified by reverse transcription-PCR from 53% (322 of 607) of fecal specimens collected from children with severe diarrhea who visited hospitals in six urban areas of South Korea in 2000 and 2001. G2 was the most frequently found G type (constituted 50.6%), followed by G1 (30.1%) and G4 (13.0%). Although the P types of high incidence were P[4] (53.1%) and P[8] (21.4%), a significant incidence of P[6] (20.2%) was also noticeable. The commonest G-and P-type combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 18 publications
4
23
0
Order By: Relevance
“…A high level of protection was reported against G1, G3, G4 and G9 with P[8], but lower efficacy was reported against G2P[4] (Salinas et al, 2005;Ruiz-Palacios et al, 2006;Vesikari et al, 2006). In this study, G2P[4] strain and P[6] were detected with a high frequency of 40.9% and 14.8%, consistent with other results from the same period (Min et al, 2004).…”
Section: Discussionsupporting
confidence: 91%
“…A high level of protection was reported against G1, G3, G4 and G9 with P[8], but lower efficacy was reported against G2P[4] (Salinas et al, 2005;Ruiz-Palacios et al, 2006;Vesikari et al, 2006). In this study, G2P[4] strain and P[6] were detected with a high frequency of 40.9% and 14.8%, consistent with other results from the same period (Min et al, 2004).…”
Section: Discussionsupporting
confidence: 91%
“…Attitudes towards entrepreneurship may be associated with a person's social background and upbringing, or what Pierre Bourdieu calls habitus (Bourdieu, 1977;1984;1988;2002). Habitus regulates social practices among groups in a similar manner as the rulebook of a game regulates interaction between the players.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Ley uses a similar comparison to a "game" that was also applied by Bourdieu, and suggests that attitudes towards work may be strategically modified to suit a The willingness to use unpaid family members is an important aspect of attitudes towards self-employment. Immigrant businesses often draw on family members as a source for labour (Light, 1972;Min, 1988). Edna Bonacich (1993) refers to the often substandard working conditions in immigrant businesses as the "other side" of ethnic entrepreneurship.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It was identified that a G4P [10] strain, two G8P[10] [9] strains, and two other strains found in Ghana were G9P [10] genotypes [4]. Only one strain, G2P [10], was identified in South Korea during a surveillance study conducted in 2000-2001 [30].…”
Section: Discussionmentioning
confidence: 98%